The effectiveness of zakat distribution on the welfare of mustahiq households based on the CIBEST Model: case study at the Muhammadiyah Zakat Institution / Khusnul Hidayah, Dalila Daud and Chianda Luwi Santri - Hidayah, Khusnul; Daud, Dalila; Luwi Santri, Chianda (Faculty of Accountancy, 2019)
Poverty is one of the humanitarian problems which is a problem in many countries including Indonesia. Islam as the religion of Rahmatan Lil Alamin, offers an important instrument to overcome this problem by utilizing the potential of zakat, infaq, and shadaqah for the poor. Seeing the poverty that is currently being felt, the type of poverty is not only in terms of the material aspects but also non-material aspects including the spiritual dimension. One of the measurement models that can be used to see the impact of distributing zakat by combining the material dimensions and spiritual dimensions is the CIBEST model. The purpose of this study is to determine the impact of the distribution of Zakat on the welfare of household mustahiq based on the CIBEST model in Lazizmu Umbulharjo Yogyakarta. LazisMu is a Zakat institution owned by Muhammadiyah organization in Indonesia, which has the role to collect and distribute zakat, infaq and shadaqa. One of the zakat programs implemented by LazisMU is productive zakat fund which is expected to improve the welfare of mustahiq (zakat recipients). Thus research is needed to describe and assess the impact of zakat given to the mustahiq by adopting the CIBEST model. This model which have been developed by Beik dan Arsyianti (2015) combines the quadrants of basic human needs which include both material and spiritual aspects. CIBEST model comprising four indices is used as tool of analysis. These indices are welfare index, material poverty index, spiritual poverty index and absolute poverty index. This study uses a descriptive quantitative approach with questionnaires and interviews methods (as primary data) to productive zakat recipients by LazisMU Umbulharjo Yogyakarta. The sample of this study was 10 Mustahiq which were divided into 9 households. The results of this study indicate that there are changes in the welfare conditions of Mustahiq households before and after receiving zakat productive funds and spiritual assistance. Before receiving zakat productive funds and spiritual assistance, there were 2 prosperous households, 6 materially poor households, and 1 absolute poor household. While after being given zakat productive funds and spiritual assistance there are changes in household conditions, namely 4 households that are categorized as prosperous, 5 conditions that are categorized as material poor and there are no households categorized as absolutely poor.